KUALITAS TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN MADRASAH ALIYAH DI KOTA BAU BAU SULAWESI TENGGARA - Israpil Israpil (Balai Penelitian dan Pengembangan Agama Makassar, 2018)
Research on the quality of educators and education personnel in MadrasahAliyah (MA) is conducted at 6 MA education institutions in Bau Bau City.Collecting data using questionnaire instruments, interview guidelines, andobservation, using a quantitative descriptive approach. The quality of MA istaken from the National Education Standards to see the achievement of thequality educators and education personnel in each MA which is the basis fordescribing its quality. The results showed that the standard values of thecomponents of educators and education personnel seen from 8 componentswith their quality achievements in the category of